MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN KEMAMPUAN MEMBACA MEMAHAMI BAHASA JERMAN SISWA - Fitriani, Fitriani; Hasmawati, Hasmawati (Universitas Negeri Makassar, 2018)
This study aims to obtain data and information about the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in reading comprehension in German. The population of this study is students of class XI IPA with a total of 146 students. The research sample was chosen randomly, namely students of class XI IPA 1, amounting to 30 students as an experimental class and class XI science 2 students totaling 30 students as a control class. Data is analyzed using t-test analysis. The results of data analysis showed that th (2.72)> tt (2.002) at the significance level of 0.05. The results show that the Cooperative Integrated Reading and Composition (CIRC) learning model is effective in reading comprehension in German